1980
DOI: 10.1121/1.384312
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of airborne sound into the earth: Frequency dependence

Abstract: Simultaneous measurements have been made of sound pressure above the ground and seismic velocity below the ground surface resulting from a source suspended in the air a variable distance from the surface. The ratio of seismic velocity to acoustic sound pressure has been determined; there are peaks in the ratio in the vicinity of 45 and 90 Hz depending on the height of the speaker. The source-receiver distance was 10, 30, and 60 m; the source height was varied between 1 and 10 m. The frequency of maximum acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…A contributing factor to this effect is the acoustic-to-seismic coupling itself. At a certain angle, Rayleigh waves may be created more efficiently, especially if the angle allows for constructive interference of surface waves (Bass et al, 1980). However, interference can also occur if the signal is reflected from a topographic feature.…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contributing factor to this effect is the acoustic-to-seismic coupling itself. At a certain angle, Rayleigh waves may be created more efficiently, especially if the angle allows for constructive interference of surface waves (Bass et al, 1980). However, interference can also occur if the signal is reflected from a topographic feature.…”
Section: Summary Of Results and Discussionmentioning
confidence: 99%
“…8d). This implies that the helicopter creates Rayleigh waves through atmospheric coupling to the ground (Bass et al, 1980). The shorter period oscillation has a period of 0.04 s in this time window and correspond to the individual pulses from the rotor blades.…”
Section: Particle Motion Analysismentioning
confidence: 98%
“…[6,19,23]. However, Bass et al [26] reported on small scale measurements of acoustic-to-seismic coupling into soil using a loudspeaker emitting continuous waves as a source and found that the magnitude of the air-coupled seismic wave was much larger than expected from elastic wave theory; they suspected that the porous nature of the ground might explain the discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our velocity-stress governing equations do not include nonlinear material effects such as tensile failure or spalling of near-surface layers that can be important for shallow buried sources [Stump, 1985], nor do they include the effects of porosity and permeability of the near-surface materials [Sabatier et al, 1986;Hickey and Sabatier, 1997]. In particular, Bass et al [1980] showed that the transmission coefficient at the ground surface for acoustic energy in the 20-300 Hz band cannot be fully described by the impedance ratio of the materials. The transmission coefficient can be at least an order of magnitude higher (up to 3 orders of magnitude higher) when permeability and airflow through pore volumes is considered.…”
Section: Finite Differencesmentioning
confidence: 99%